2016
DOI: 10.1016/j.apjtm.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents, cytotoxic, antifungal and antimicrobial properties of Centaurea diluta Ait. subsp. algeriensis (Coss. & Dur.) Maire

Abstract: All the isolated compounds were described for the first time from this species. Although inactive against 7 tested microorganisms (fungi, bacteria and yeast, human or plant pathogens), the raw extract was able to potentiate the effect of beta-lactam antibiotics on methicillin-resistant Staphylococcus aureus (MRSA), reducing the minimal inhibitory concentrations (MICs) by a factor of 2-32-fold. No synergy was found between the extract and streptomycin. From the five isolated compounds only jaseosidin 5 showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…For example, in the studies of Zater et al, raw chloroform extract of Centaura diluta subsp. algeriensis were investigated for cytotoxicity, and showed that the viability of A549 cells was reduced with the IC 50 value of 21 µg/ml [39]. In contrast to the above result, in the current study it was found that the IC 50 value of nine µg/ml on the same cell line, indicating that chloroform extract of C. babylonica (L.) L. is more effective against A549 cells than that of C. diluta subsp.…”
Section: Discussioncontrasting
confidence: 93%
“…For example, in the studies of Zater et al, raw chloroform extract of Centaura diluta subsp. algeriensis were investigated for cytotoxicity, and showed that the viability of A549 cells was reduced with the IC 50 value of 21 µg/ml [39]. In contrast to the above result, in the current study it was found that the IC 50 value of nine µg/ml on the same cell line, indicating that chloroform extract of C. babylonica (L.) L. is more effective against A549 cells than that of C. diluta subsp.…”
Section: Discussioncontrasting
confidence: 93%
“…Compound 1 is a frequently occurring flavone reported as a constituent of several Centaurea species ( Mouffok et al, 2012 ). However, we are reporting here for the first time its isolation from C. ragusina L. Different bioactivities have been reported for compound 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported in the literature that ARG inhibits the proliferation of retinoblastoma Y79 and promotes apoptosis by downregulating JAG-1 [ 11 ]. Although previous studies have demonstrated that ARG inhibits glioma cell proliferation and induces cell cycle arrest and apoptosis [ 14 , 15 ], the target and mechanism of ARG for the treatment of glioma are still not deep enough, and we need to use further experiments to explore so that we can provide new options for the treatment of glioma.…”
Section: Introductionmentioning
confidence: 99%